1977
DOI: 10.1083/jcb.74.2.414
|View full text |Cite
|
Sign up to set email alerts
|

Release of poly a(+) messenger RNA from rat liver rough microsomes upon disassembly of bound polysomes

Abstract: Several procedures were used to disassemble rat liver rough microsomes (RM) into ribosomal subunits, mRNA, and ribosome-stripped membrane vesicles in order to examine the nature of the association between the mRNA of bound polysomes and the microsomal membranes. The fate of the mRNA molecules after ribosome release was determined by measuring the amount of pulse-labeled microsomal RNA in each fraction which was retained by oligo-dT cellulose or by measuring the poly A content by hybridization to radioactive po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

1978
1978
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 38 publications
1
41
0
Order By: Relevance
“…Previous studies attempted to address whether there is translation-independent mRNA association with the ER using cellular fractionation techniques. Because harsh chemical conditions were required to disassociate ribosomes from ER derived vesicles, which might disrupt the potentially delicate mRNA-ER association, these studies were inconclusive, providing evidence for [5][6][7][8] and against 9,10 ribosomal-independent anchoring of mRNA to the ER.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies attempted to address whether there is translation-independent mRNA association with the ER using cellular fractionation techniques. Because harsh chemical conditions were required to disassociate ribosomes from ER derived vesicles, which might disrupt the potentially delicate mRNA-ER association, these studies were inconclusive, providing evidence for [5][6][7][8] and against 9,10 ribosomal-independent anchoring of mRNA to the ER.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, analyses of in situ mRNA-ER interactions conducted with rough microsomes (RM) have demonstrated that ER-associated mRNAs can be binned into two broad classes: those that are bound via ribosome-dependent (indirect) and those that undergo ribosome-independent (direct) ER-mRNA anchoring (Fig. 1A) (13,15,(45)(46)(47). These differences are significant because they suggest that mRNA localization and anchoring to the ER is selective and regulated and so may contribute significantly to gene expression.…”
Section: Divergent Modes Of Ribosome-mrna Association With the Ermentioning
confidence: 99%
“…First, tissue culture cells are permeabilized with a digitoninsupplemented cytosol buffer to permeabilize the plasma membrane and release the cytoplasmic mRNA pool (28,49). The digitonin-permeabilized (semi-intact) cells are then treated with salts, chelating agents, and/or detergents, and mRNA-ER interactions were assessed by examining the mRNA composition of the released and ER-associated fractions (13,15,(45)(46)(47). Using HeLa cells as a model, we first examined the ER association properties of two mRNAs, B2M (a secretory protein) and GRP94 (a resident protein of the ER lumen), because previous studies with RM had identified these mRNAs as undergoing either ribosome-dependent (B2M) or ribosome-independent (GRP94) membrane association (13,15).…”
Section: Divergent Modes Of Ribosome-mrna Association With the Ermentioning
confidence: 99%
“…For the isolation of free and membrane-bound polysomes the procedures of Scheele et al [6], Kruppa and Sabatini [7] and Shore and Tata [8] were combined and modified as previously described [9]. The sedimented free polysomes were dissolved in 0.2 M Tris/HCI buffer, pH 8.5, 50 mM KC1, 10 mM MgCI,, 2.5 mM dithiothreitol and 20 mM EDTANa,, incubated at 0°C for 1 h, added onto a linear sucrose gradient (20 -40%) in the above buffer and centrifuged in a Beckman SW27 rotor at 27000 rpm for 27 h. The fractions of the gradient indicated in Fig.…”
Section: Preparation Of Free and Membrane-bound P M R N P Particlesmentioning
confidence: 99%